Hubungan Status Sosial Ekonomi Orang Tua Dengan Prestasi Akademik Siswa Kelas V Sekolah Dasar di Kecamatan Peranap - Qonita Azka; Febrina Dafit (Jayapangus Press, 2026)
The socioeconomic background of families is often assumed to be related to the academic achievement of elementary school students, yet empirical findings on this relationship remain mixed. This study aims to examine the relationship between parental socioeconomic status and the academic achievement of fifth-grade elementary school students in Peranap District. A quantitative approach with a correlational design was employed. Using a saturated sampling technique, 50 fifth-grade students from SDN 004, SDN 006, and SDN 017 Baturijal Hulu were involved. Parental socioeconomic status was measured through a questionnaire covering five indicators (parental education, occupation, income, learning facilities, and parental support), while academic achievement was obtained from students’ report card scores. The questionnaire’s Likert-scale items were tested for validity, resulting in 19 valid items, and for reliability with a Cronbach’s Alpha of 0.889. Data were analyzed using the Pearson Product Moment correlation after the assumptions of normality (Kolmogorov-Smirnov, sig. 0.149 and 0.664 > 0.05) and linearity had been met, with no extreme outliers detected. The analysis yielded a correlation coefficient of 0.880 (p < 0.001), indicating a very strong and significant positive relationship, so that the alternative hypothesis was accepted. The coefficient of determination (77.4%) is interpreted as the proportion of variance in academic achievement statistically associated with parental socioeconomic status, not as evidence of a direct causal effect. As the design is correlational, the findings should be understood as associations rather than cause-and-effect relationships.